Análisis con fines de mejora de la cadena de suministro de la Compañía Grupo Carolina Práxedis de Artunduaga S.A.S (2024)
Multinational organizations regularly recognize and apply the strategies and advantages of an adequate supply chain management. However, in Colombia, companies tend to operate empirically and usually do not use any supply chain management related theorie. Consequently, they present a endless of difficulties in this area. Consequently, the present research work aims to provide a series of proposals, supported by the theory of the Supply Chain Management framework proposed by Lambert and Cooper (2000), offering a proposed solution to the problems encountered. The framework allows addressing the management components, the structure of the chain network and the key business processes identified by these authors. This case study was developed in the company Grupo Carolina, Práxedis de Artunduaga S.A.S., located in the city of Ibagué. The research team focused on two key business processes: Supplier Relationship Management and Customer Service Management, considered critical for the Company, taking into account the evaluation of all processes and the current state of the Company.Additionally, the implementation of the framework was based on the Lean Six Sigma methodology under the Define, Measure, Analyze, Improve and Control (DMAIC) process. This allowed producing an implementation plan and other internal documents that will be inputs for other organizations interested in this area.